Unethical Marketing Practices by Petroleum Marketers in Nigeria - Glory, Basil (British Journal of Marketing Studies, 2016)
The study focused on unethical marketing practices by petroleum marketers in Nigeria. It was motivated by the reported cases of manipulations of prices and products by dealers of petroleum products in the market. The objectives of the study were to: examine the effect of unethical pricing by petroleum marketers on motorists in Nigeria; and determine the correlation between fuel adulteration by marketers and the rate of cars/vehicles’ engines damages in the country. Survey and desk research designs were adopted, hence, both secondary and primary data for the analysis. The area of study for the desk research was based on two geographical structures of the country as North and South, where some States were selected for the study; while Calabar the capital of Cross River State was used for the primary data. From a population of 2,500 motorists that patronize 10 selected filling stations regularly in Calabar, a sample size of 333 was determined at 5 percent margin of error and 95 percent level of confidence. The statistical tools of chi-square and correlation coefficient were used to test the hypothesis. The findings indicated that: unethical pricing of petroleum by marketers had significant negative effect on motorists in Nigeria, and fuel adulteration by marketers significantly affects the rate of cars/vehicles’ engines damages in the country. Based on this, the study recommended that relevant law enforcement agencies should improve on their monitoring and enforcement efforts geared towards checkmating unethical marketing of petroleum products in Nigeria.